2020
DOI: 10.1007/978-3-030-14625-2
|View full text |Cite
|
Sign up to set email alerts
|

Handbook on Promoting Social Justice in Education

Abstract: material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dumas and Ross (2016) further argued that Black youth bodies in the school system are viewed as representative of the ultimate threat to authority, and that the disciplining of Black youth is understood as the definitive reinforcement of security and order. Lopez (2019) suggested that the over disciplining of Black youth is an expression of anti-Black racism. Lopez further argued that within the context of anti-Black racism, punishment is primary and foundational to Black subjection, with discipline as a popular aspect of cruelty.…”
Section: Bill 212 and The Negative Impact On Black Studentsmentioning
confidence: 99%
“…Dumas and Ross (2016) further argued that Black youth bodies in the school system are viewed as representative of the ultimate threat to authority, and that the disciplining of Black youth is understood as the definitive reinforcement of security and order. Lopez (2019) suggested that the over disciplining of Black youth is an expression of anti-Black racism. Lopez further argued that within the context of anti-Black racism, punishment is primary and foundational to Black subjection, with discipline as a popular aspect of cruelty.…”
Section: Bill 212 and The Negative Impact On Black Studentsmentioning
confidence: 99%